Cutaneous, metastasizing yolk sac tumor. - Santoro, N.; De Leonardis, F.; Greco, I.; Mancino, A.; Novielli, C. (European Journal of Pediatric Dermatology, 2007)
A case of cutaneous metastasizing yolk sac tumor in a 20-month-old girl is reported.